Analisis Kinerja Pegawai di Kantor Kecamatan Sarang Kabupaten Rembang - Pranesia Kurniawati; Nina Widowati; Aloysius Rengga (Journal of Public Policy and Management Review, 2014)
This research is proposed to analyze and describe the official performance at Sarang Sub district Rembang Regency and what is the performance dimension that support and obstruct official performances of Sarang Subdistrict Rembang Regency. This research is descriptive qualitative research type with interviews, observations, documentation and literary study as the techniques of collecting data. Informants are chosen from the officers at Sarang Sub district Rembang Regency.This research, the researcher uses eight dimension of Faustino Cardoso Gomes. Job knowledge dimension is good enough, officer understand the vision and the mission of their instancy and also understand their job description. Cooperation dimension is good enough; between the leader and officer already have a good kindship. Initiative is good enough, officers are already choose priority that must do it earlier and react about assignment that given by leader. Personal Qualities is good enough, officer often overtime work to finish the job. Quality of work dimension is less because the officer’s readiness and responsiveness is less when they do their main job and function, the less experienced officer and numbers of assignn which are given. Quality of work dimension is not good enough, because it hampered with the differences of work load and less number officer. Creativeness dimension is also not good enough, the officer still not give ideas to finished the work problem. Dependability dimension is not good enough because there is some officer that leave their office when the leader is not in the office.Based on the results of the research, it can be concluded that the official works of Sarang Sub district Rembang Regency office is not good enough or optimal. The not optimal of work officer because there are some less experience officer, less of facilities and infrastructures, less of creativities and no firmness of the leader. So, at Sarang Sub district Rembang Regency office is need for additional computer, providing training, firmness of the leader to their officer.